Marketing Strategy for Education Services in Attracting New Students at Nurul Yaqin Tanjung Batu High School - Andri Cahyo Purnomo; Wilda Widiawati; Maria Jashinta Elisabet Hamboer; Bambang Irawan; Fitri Hidayati (LP2M IAIN Sultan Amai Gorontalo, 2022)
The purpose of this study was to determine the marketing strategy of educational services in attracting new students at Nurul Yaqin High School in Tanjung Batu. The problems that occur are the time management is not right, the distribution of brochures is not effective, the marketing reach is not wide, and the number of people/parents of students who do not master Information Technology (IT) in the registration of new students. This study uses a qualitative method by using the type of field research field. The informants in this study were the principal, the head of the new student admissions committee, the new student admissions committee, parents, and students. Data collection techniques use the method of observation, interviews, and documentation. Technical analysis of data in this study using data reduction, data presentation, and data verification. The results of the study indicate that the marketing strategy of educational services in attracting new students at Nurul Yaqin Tanjung Batu High School, Ogan Ilir Regency can be said to have been going well in terms of the target market strategy of the market segment. Strategy implementation is done by direct socialization. In terms of competitive position strategy, Nurul Yaqin High School has uniqueness and advantages. Meanwhile, in the case of a mixed strategy, the education marketing strategy is well implemented.